Understanding evidence use by decision-makers: Findings of an online survey - Zhang, Wei; Li, Taotao; Carmona, Natalia Estrada; Remans, Roseline; Whitney, Cory; Aynekulu, Ermias; Dickens, Chris; Elias, Marlène; Jones, Sarah; Langan, Simon; Luedeling, Eike; McGonigle, Daniel; et al. (International Food Policy Research Institute, 2021)
Lack of evidence to support decision-making constitutes one of the obstacles to effective and socially responsive development policies. Making evidence-based decisions in multi-objective policies or programs is dependent on access to and use of relevant and coherent evidence. However, many potential obstacles may compromise decision-makers’ access to and use of evidence. Our work aims to improve the way research supports and program decision-makers involved in landscape initiatives in achieving sustainability across environmental, social, and economic domains. We designed an online survey to assess barriers hampering access to evidence and to explore avenues to reduce these barriers. Here we report on the findings of the survey, outline barriers to use of evidence, and suggest ways to reduce or remove those barriers.